PENINGKATAN KEMAMPUAN MENULIS CERPEN DENGAN MENGGUNAKAN MODEL EXPERIENTIAL LEARNING SISWA KELAS X 1 SMA NEGERI 3 LUBUKLINGGAU - Sadarti Eliyani (Universitas Bengkulu, 2016)
The purpose of this reserch to knew the increasing ability of the students in writing short story the eleventh grade students of SMA Negeri 3 Lubuklinggau by using experiential learning. The kind of this reserch was the class action reserch with two cycles; every cycle had planning, action, observation, and reflection. The data of this reserch was given from the ability of the students in writing short story and observation. The technique colleting the data in this reserch was from theability of the students in writing short story, observation, and documentation. The result of this reserch showed the rising students’ ability, the average cycle 1 was 75 good categories and the average cycle II was 85 very good categories. The conclusion of the reserch was model experiential learning could rise the students score in writing short story the eleventh grade students of SMA Negeri 3 Lubuklinggau.Kata Kunci: Writing, short story, and model experiential learning.